Halogen bonding (X‐bonding): A biological perspective. (29th December 2012) - Scholfield, Matthew R.; Zanden, Crystal M. Vander; Carter, Megan; Ho, P. Shing
Abstract The concept of the halogen bond (or X‐bond) has become recognized as contributing significantly to the specificity in recognition of a large class of halogenated compounds. The interaction is most easily understood as primarily an electrostatically driven molecular interaction, where an electropositive crown, or σ‐hole, serves as a Lewis acid to attract a variety of electron‐rich Lewis bases, in analogous fashion to a classic hydrogen bonding (H‐bond) interaction. We present here a broad overview of X‐bonds from the perspective of a biologist who may not be familiar with this recently rediscovered class of interactions and, consequently, may be interested in how they can be applied as a highly directional and specific component of the molecular toolbox. This overview includes a discussion for where X‐bonds are found in biomolecular structures, and how their structure–energy relationships are studied experimentally and modeled computationally. In total, our understanding of these basic concepts will allow X‐bonds to be incorporated into strategies for the rational design of new halogenated inhibitors against biomolecular targets or toward molecular engineering of new biological‐based materials.